Evaluasi potensi mata air dalam pemenuhan kebutuhan air bersih Desa Baumata Kecamatan Taebenu, Kabupaten Kupang - Theresia Beatrix Kameo; Didik Taryana; Ike Sari Astuti (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
The need for clean water is needed to meet daily water needssuch as drinking, cooking, bathing, washing, watering plants and others. Sources of clean water used for daily needs in general must meet quantity and quality standards. Geographical conditions, population size, and socio-economic conditions are closely related to the fulfillment of clean water needs and the quantity and quality of clean water in the region. The research location for Baumata Village is in the administrative area of the Taebanu Kupang. This study uses a survey method. In analyzing the potential of the Baumata spring using this method, it is necessary to collect quantity and quality data that aims to evaluate the potential of the spring in fulfilling the need for clean water. From the results obtained by the Baumata spring, namely the quality of the water is appropriate or according to the standard for clean water quality, based on the yield and quantity of water it can meet the needs of clean water based on a yield of 0.0434 m3/liter or equal to 156,240 liters/second. The supply of clean water needs in Baumata village based on research results is fulfilled, it can be seen in the results of Q more than equal to sigma Ka (156,240 more than equal to 117,413) this shows that the spring discharge is sufficient for the clean water needs of the daily/capita population in meeting the clean water needs of individuals in Baumata Village. Kebutuhan akan air bersih sangat di perlukan dalam memenuhi kebutuhan air harian seperti minum, masak, mandi, mencuci, menyiram tanaman maupun lainnya. Sumber air bersih yang digunakan untuk kebutuhan hidup harian secara umum harus memenuhi standar kuantitas dan kualitas. Kondisi geografi, jumlah penduduk, dan sosial ekonomi sangat erat berpengaruh terhadap pemenuhan kebutuhan air bersih, serta kuantitas dan kualitas air bersih pada wilayah tersebut. Lokasi penelitian Desa Baumata berada pada wilayah administrasi Kec. Taebanu Kap. Kupang. Penelitian ini menggunakan metode survey. Dalam menganalisis potensi mata air Baumata menggunakan metode ini perlu menggumpulkan data kuantitas dan kualitas yang bertujuan untuk mengevaluasi potensi mata air dalam pemenuhan kebutuhan air bersih. Dari hasil yang didapatkan mata air baumata yaitu kualitas air layak atau sesuai standar baku mutuh air bersih, berdasarkan hasil dan kuantitas air dapat memenuhi kebutuhan air bersih bersadarkan hasil 0,0434 m3/liter atau sama dengan 156.240 liter/detik. Suplai kebutuhan air bersih pada Desa Baumata berdasarkan hasil penelitian terpenuhi, dapat dilihat pada hasil Q lebih dari sama dengan sigma Ka (156.240 lebih dari sama dengan 117.413) hal ini menujukan bahwa debit mata air mencukupi kebutuhan air bersih penduduk harian/kapita dalam pemenuhan kebutuhan air bersih perindividu di Desa Baumata.